Board Game Sebagai Media Komunikasi Visual Pendekatan Hubungan Harmonis Keluarga Antar Orang Tua Dan Anak - Rahmatilani, Conny; Patriansah, Mukhsin (UNIVERSITAS INDO GLOBAL MANDIRI, 2024)
Abstract: Time with family is hard to come by if parents are busy working, making parents pay less attention to the importance of inviting their children to play games. Parents should set aside some of their time to get together and play games together. There are many benefits from playing with children, one of which is that the relationship between parents and children will be closer and they can learn to work together. The more time you spend with your family, the stronger the bonds that are formed to get to know each other's characters, and can train children's abilities. One medium that can increase harmony in the family is a board game. Board Game is a type of game in which one of the components is a square sheet like a board whose materials can vary, but generally made of thick cardboard, such as Monopoly, Chess, Ludo and Snakes and Ladders. Board Game is a game that is suitable to be played with all family members, and can help improve family harmony. The design of the Board Game that will be designed is a Board Game that can be played with family members which aims to increase harmony in the family by giving punishments for each card that the player members get when playing the Board Game. The punishment given contains positive things for every player. Keywords: Harmonious Family, Board Game, Game